Kaji Ulang Pelaksanaan JAMSOSTEK Menurut UU No. 3 Tahun 1992 (Studi Kasus di PT TELKOM DIVRE III Bandung) - Jum Anggriani (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Labors as one ofthe agents of development makes a huge contribution in establishing of nationai production and sociai welfare. This sector aiso contributes a tremendous foreign income to the state. However, it is normal to grant protection to the labors to achieve better welfare conditions. The protections may consist of protection to gain employment. The right of the employees to health care, safe work environment, protection of wage andguarantee social security.